Probability-based estimate of tropical cyclone damage: An explicit approach and application to Hong Kong, China. (15th July 2018) - Wang, Cao; Zhang, Hao
Highlights: An explicit approach is developed to evaluate the tropical cyclone (TC) damage. A TC vulnerability model is developed for Hong Kong, China, using historical data. The applicability of the method is demonstrated through an illustrative example. Abstract: Tropical cyclones (TCs) are among the most costly natural hazards affecting civil construction in coastal areas, which have caused extensive economic losses and social disruption world-widely. Moreover, the intensity and/or frequency of future TCs have been projected to change with time due to the potential impacts of climate change, indicating the potential of ever larger TC damages for coastal regions. The estimate of future TC damage should be conducted under a probability-based framework, taking into account the uncertainties associated with both the TC characteristics (e.g., intensity and frequency) and the vulnerability of the coastal communities of interest. In this paper, an explicit approach is developed to evaluate the TC damage for TC-prone areas considering the potential impacts of climate change. The mean value and variance, as well as the cumulative density function of cumulative TC damage are estimated quantitatively. The proposed method is applied to TC damage assessment of Hong Kong, China – a TC-prone area which has suffered severely from historical cyclones. Sensitivity analysis is also performed to investigate the impacts of the time-variant characteristics of both the TC process and the TC damage conditional on one TC event on the cumulative damage costs for coastal areas.